Peningkatan Literasi Numerasi Siswa MTs melalui Penerapan Escape Room Mathematics pada Materi Statistik - Adi Irawan; Dwi Agustini; Zulfiani Rohmah; Leny Fitriah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to evaluate the effectiveness of escape room mathematics in improving the numeracy literacy of grade VII students in MTs, as well as assess its influence on critical, collaborative, and reflective thinking skills. The research was conducted using the Classroom Action Research (CAR) approach using the plan-act-observe-reflect cycle, involving 30 students who were selected purposively. Data were collected through numeracy literacy tests before and after learning, student engagement observations, and motivational questionnaires. The results showed a clear increase in numeracy literacy, with an average pre-test score of 58 increasing to 78 in the post-test, as well as a consistent increase between cycles. In addition to strengthening the understanding of statistical concepts, the application of escape room mathematics has also succeeded in developing students' critical, collaborative, and reflective thinking skills. These findings confirm that this method is effective as an innovative learning strategy to improve students' numeracy literacy, learning motivation, and social skills.